The Impact of Accounting Software Use on Financial Report Efficiency - Sutarni; Budiandru; Loso Judijanto; Gema Ika Sari; Sukriyah (Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid development of information technology has encouraged organizations to transition from manual accounting systems to digital platforms to improve accuracy, speed, and decision-making quality. However, the adoption of such systems remains uneven, particularly among SMEs in developing countries. This study aims to analyze how accounting software influences financial reporting efficiency and to identify factors affecting its effective implementation. This research employs a qualitative approach using a literature review method, drawing on secondary data from academic journals, books, and credible reports. Data were collected through systematic documentation and analyzed using content analysis techniques to synthesize relevant findings. The results indicate that accounting software significantly enhances reporting efficiency by automating processes, reducing errors, and accelerating report generation. Additionally, it improves cost efficiency and resource utilization. However, the effectiveness of implementation depends on human resource competence, organizational support, and technological readiness. Challenges such as high initial costs and limited digital literacy remain critical barriers. The study implies that organizations should adopt a comprehensive approach by combining technological investment with human resource development and organizational support.